An Analysis of the Implementation of Civil Servant Mutations, Rotations, and Promotions in the Regional Government of Bengkulu Province - Permata, Syilva Dwi Intan; Lorita, Evi; Saputra, Harius Eko (Social Sciences Journal, 2025)
This study aims to analyze the implementation of civil servant mutation, rotation, and promotion policies within the Regional Government of Bengkulu Province, specifically in the Bureau of Governance and Public Welfare. Mutation, rotation, and promotion are key components of civil service management, aiming to optimize personnel distribution, develop competencies, and enhance employee motivation and performance. The study uses a qualitative approach with data collected through observation, in-depth interviews, and documentation. Informants included structural officials, functional officers, and staff who have undergone mutation or promotion. The theoretical framework refers to the Indonesian Civil Service Agency Regulation No. 5 of 2019, which outlines seven key indicators: competence, career pattern, employee mapping, talent pool, career development, performance and behavior evaluation, and organizational needs. The results show that while most processes adhere to the regulation, there are still several challenges, such as limited employee mapping data, mismatches between educational background and new positions, and lack of training prior to job transfer. Furthermore, non-technical factors such as personal connections and subjective considerations still influence placement decisions. These findings highlight the need to strengthen a merit-based system grounded in transparency and performance to build a professional and effective bureaucracy. This study is expected to contribute valuable insights for the Bengkulu Provincial Government in refining its civil servant mutation and promotion practices to be more fair, objective, and strategically aligned with organizational goals.